3GPP LTE‐Assisted Wi‐Fi‐Direct: Trial Implementation of Live D2D Technology. Issue 5 (1st October 2015) - Pyattaev, Alexander; Hosek, Jiri; Johnsson, Kerstin; Krkos, Radko; Gerasimenko, Mikhail; Masek, Pavel; Ometov, Aleksandr; Andreev, Sergey; Sedy, Jakub; Novotny, Vit; Koucheryavy, Yevgeni
Abstract : This paper is a first‐hand summary on our comprehensive live trial of cellular‐assisted device‐to‐device (D2D) communications currently being ratified by the standards community for next‐generation mobile broadband networks. In our test implementation, we employ a full‐featured 3GPP LTE network deployment and augment it with all necessary support to provide real‐time D2D connectivity over emerging Wi‐Fi‐Direct (WFD) technology. As a result, our LTE‐assisted WFD D2D system enjoys the required flexibility while meeting the existing standards in every feasible detail. Further, this paper provides an account on the extensive measurement campaign conducted with our implementation. The resulting real‐world measurements from this campaign quantify the numerical effects of D2D functionality on the resultant system performance. Consequently, they shed light on the general applicability of LTE‐assisted WFD solutions and associated operational ranges.